Expresion of Tumor Necrosis Factor Alfa (TNF-α) in The Pancreas of Diabetic Mice (Mus musculus) Following Adminstration of Catharantus roseus Extract - Nunun Ainun Putri Sari Banun Kaliky; Mechiavel Moniharapon; La Eddy (Biofaal Journal, 2025)
Catharanthus roseus is a plant that contains compounds such as alkaloids, flavonoids, saponins, and carotenoids, which act as antioxidants. This study aimed to investigate the effect of Catharanthus roseus extract on the reduction of TNF-α expression in the pancreas of diabetic mice (Mus musculus). In this study, mice with an average body weight of 30 g were induced with streptozotocin (0.1 ml/BB) to induce diabetes mellitus. Subsequently, the diabetic mice were administered Catharanthus roseus extract, using methanol and petroleum benzene solvents at a concentration of 5%, with a dose volume of 1.5 ml/BB, for 14 days. On the final day, the mice were sacrificed, and the pancreas organs were collected, followed by histological preparation using immunohistochemistry methods. The results indicated that administration of Catharanthus roseus extract with methanol and petroleum benzene solvents reduced TNF-α expression. The Catharanthus roseus extract with methanol solvent was more effective in lowering TNF-α expression.